Dispersal Limitation Expands the Diversity of Coral Microbiome Metacommunity in the South China Sea - Zhang, Jiandong; Hu, Anyi; Sun, Yingting; Yang, Qingsong; Dong, Junde; Long, Lijuan; Huang, Sijun (Frontiers in Marine Science, 2021)
The coral microbiome is one of the most complex microbial biospheres. However, the ecological processes shaping its assembly are not well understood. Here, we investigated the abundance, diversity, and community assembly mechanisms of coral-associated microbes from a highly diverse coral metacommunity in the South China Sea. Compared to seawater, the coral microbial metacommunity was defined by highly variable bacterial abundances among individual coral samples, high species evenness but not high species richness, high β-diversity, and a small core microbiome. We used variation partitioning analysis, neutral community model, and null model to disentangle the influences of different ecological processes in coral microbiome assembly. Measured physico-chemical parameters of the surrounding seawater and spatial factors together explained very little of the variation in coral microbiome composition. Neutral processes only explained a minor component of the variation of coral microbial communities, suggesting a non-stochastic community assembly. Homogeneous and heterogeneous selection, but not dispersal, contributed greatly to the assembly of the coral microbiome. Such selection could be attributed to the within-host environments rather than the local environments. Our results demonstrated that dispersal limitation and host filtering contribute significantly to the assembly of discrete coral microbial regimes and expand the metacommunity diversity.